2023
DOI: 10.1136/bmjopen-2022-067296
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between caregiver competence, burden and health-related quality of life among Chinese family caregivers of elderly adults with disabilities: a cross-sectional study using structural equations analysis

Abstract: ObjectiveTo examine the relationship between caregiver competence and health-related quality of life (HRQoL) among family caregivers of disabled elderly adults, and to evaluate the role of caregiver burden as a potential mediator of that relationship.DesignCross-sectional study.SettingTwo general hospitals in Shanghai, China.ParticipantsStudy participants were 135 family caregivers of disabled elderly adults listed on a roster for outpatient and emergency services utilisation from January to March 2022.Data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…This indicates that the path analysis model has good fit (Table 5 ) . The model parameters demonstrated that the fitting effect of the model was acceptable 50 . The model was continuously revised by referring to the model fitting degree, and the influencing factors for AD were finally included in the path analysis.…”
Section: Resultsmentioning
confidence: 83%
“…This indicates that the path analysis model has good fit (Table 5 ) . The model parameters demonstrated that the fitting effect of the model was acceptable 50 . The model was continuously revised by referring to the model fitting degree, and the influencing factors for AD were finally included in the path analysis.…”
Section: Resultsmentioning
confidence: 83%